Strategi Public Relation Dalam Membangun Citra Baik Lembaga SMK NU Tulungagung - Ahmad Muzakka (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
In addition to the academic community (internal public), the community (external public) also contributes to public relations strategies, specifically the relationship between schools and the public (society) that is designed to foster cooperation in order to gain recognition from the community and improve the quality of education. Therefore, to develop the educational institution, SMK NU Tulungagung must manage public relations. Specifically, this means overseeing school activities and improving school achievements, which will then be shared on social media as an effort to attract the attention of a wider audience. This study aims to explain the public relations approach used to improve the positive perception of the institution toward SMK NU Tulungagung. The research uses a qualitative methodology and is classified as a case study. Three methods are used to collect data: documentation, interviews, and observations. The data analysis stages include data condensation, data presentation, and verification and conclusion drawing. Based on the research findings, the public relations strategy of SMK NU Tulungagung consists of four main steps: program planning, organizing, implementation, and reporting/evaluation. Planning involves identifying issues and program planning based on problem analysis; organizing involves appointing administrators and granting authority to those involved in public relations program activities; communication with strategies is used to implement the program, and program assessment and reporting. Based on the findings of this study, educational institutions must establish and implement a strategic plan that aligns with the vision, mission, and objectives of their internal and external environment. When an institution implements a good and appropriate approach, it becomes part of its branding, giving it a reputation and advantage over other similar organizations. The obstacles in the public relations strategy to build a good institutional image at SMK NU Tulungagung include miscommunication, as some people in the surrounding community still lack concern for children's education due to a lack of motivation within the community. As a result, when school representatives come, they are less responsive in conveying information related to students. Every action taken by the educational institution will undoubtedly create challenges and consequences. The challenges of the public relations strategy in building a good institutional image at SMK NU Tulungagung include an increase in the registration of new students and public recognition of the school’s existence.